The Relationship Between Parenting Patterns and Disease Patterns with the Incident of Stunting in Toddlers 6-36 Months at the Panyabungan Jae Community Health Center, Panyabungan District, Mandailing Regency, Christmas 2022 - Nita, Surya (Benih : Journal of Midwifery, 2023)
This study aims to analyze the relationship between parenting patterns, disease patterns, and the incidence of stunting among toddlers aged 6-36 months at the Panyabungan Jae Community Health Center, located in the Panyabungan District, Mandailing Natal Regency, in 2022. Employing an observational study design, the research involved 200 toddlers and their mothers as respondents. Data were collected through interviews with mothers to assess parenting patterns applied at home and to record the history of illnesses experienced by toddlers. Statistical analysis, including the chi-square test, was conducted to evaluate the relationship between parenting styles, disease patterns, and the incidence of stunting in toddlers. The study results revealed a significant relationship (p < 0.05) between parenting patterns, disease patterns, and the occurrence of stunting. Parenting patterns that do not cater to the needs of children's growth and development, such as inadequate diet, poor personal hygiene practices, and insufficient developmental stimulation, were associated with an increased risk of stunting in toddlers. Additionally, common disease patterns experienced by toddlers, such as respiratory tract infections and digestive disorders, were identified as contributing factors to stunting. These findings offer valuable insights into the multifaceted factors influencing children's growth and development during early childhood. The practical implication of this research underscores the importance of adopting a holistic approach to prevent stunting, which includes educating parents about effective parenting practices, disease prevention strategies, and ensuring adequate access to healthcare services to address common health issues experienced by toddlers.